Turn-Taking Organization in a Classroom Interaction: A Conversation Analysis at MAS Mu’allimin NW Gunung Rajak - Sari, Dewi Purnama; Gufron, Moh.; Hadi, Marham Jupri (Journey: Journal of English Language and Pedagogy, 2026)
This study examines turn-taking organization in classroom interaction in MAS Mu’allimin NW Gunung Rajak through the lens of Conversation Analysis (CA) approach.. This qualitative study collected data through classroom observations and audio recordings in a grade XI science class. The analysis focused on the strategies of taking the turn, holding the turn, and yielding the turn  based on the theory of Anna-Brita Stenström theory. The findings revealed that classroom interaction was dominated by the teacher through strategies such as starting up, turn allocation, repair, and clarification, while students mostly participated through short responses, interruptions, and overlap. The study concludes that turn-taking organization plays a crucial role in maintaining effective classroom communication, although the interaction remained predominantly teacher-centered.